The Point Digit II: Mechanical Design and Testing of a Ratcheting Prosthetic Finger. (25th January 2021) - Segil, Jacob L; Pulver, Ben; Huddle, Stephen; Weir, Richard F ff; Sliker, Levin
ABSTRACT: Introduction: People with partial hand loss represent the largest population of upper limb amputees by a factor of 10. The available prosthetic componentry for people with digit loss provide various methods of control, kinematic designs, and functional abilities. Here, the Point Digit II is empirically tested and a discussion is provided comparing the Point Digit II with the existing commercially available prosthetic fingers. Materials and Methods: Benchtop mechanical tests were performed using prototype Point Digit II prosthetic fingers. The battery of tests included a static load test, a static mounting tear-out test, a dynamic load test, and a dynamic cycle test. These tests were implemented to study the mechanisms within the digit and the ability of the device to withstand heavy-duty use once out in the field. Results: The Point Digit II met or exceeded all geometric and mechanical specifications. The device can withstand over 300 lbs of force applied to the distal phalange and was cycled over 250, 000 times without an adverse event representing 3 years of use. Multiple prototypes were utilized across all tests to confirm the ability to reproduce the device in a reliable manner. Conclusions: The Point Digit II presents novel and exciting features to help those with partial hand amputation return to work and regain ability. The use of additive manufacturing, unique mechanism design, and clinically relevant design features provides both the patient and clinician with a prosthetic digit, which improves upon the existing devices available.